2021
DOI: 10.14639/0392-100x-n0881
|View full text |Cite
|
Sign up to set email alerts
|

Application of a symptoms score questionnaire after conjunctivodacryocystorhinostomy: outcomes

Abstract: Objective. To evaluate medium/long term outcomes and patient satisfaction through relief of symptoms and improved quality of life (QoL) after Jones tube conjunctivodacryocystorhinostomy (JT-CDCR) using the Naso Lacrimal Duct Obstruction symptom-score (NLDO-SS). Methods. We conducted a retrospective, non-comparative, multicentric study including patients with complete obstruction of the superior and inferior proximal lacrimal drainage system. All patients underwent JT-CDCR, and the patency of the tube was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Lattice parameters of Ce 4.67 Si 3 O 13 , Ce 2 O 2 S, CeS, and δ-Fe. [50][51][52][53] Substance Space group a…”
Section: Modification Mechanism Of Cerium On Solidification Structurementioning
confidence: 99%
“…Lattice parameters of Ce 4.67 Si 3 O 13 , Ce 2 O 2 S, CeS, and δ-Fe. [50][51][52][53] Substance Space group a…”
Section: Modification Mechanism Of Cerium On Solidification Structurementioning
confidence: 99%
“…Recent studies have explored the potential of lacrimal duct bypass surgery by implantation of bypass tubes and other surgical methods [10][11][12] . However, the popularization and application of lacrimal duct bypass prosthesis are limited because of its disadvantages such as easy shedding and inflammatory reaction [13][14] . The studies [15][16][17] reported a conjunctival dacryocystorhinostomy combined with bypass tube intubation, using autologous labial mucosa or saphenous vein tissue as the lining of the graft.…”
Section: Introductionmentioning
confidence: 99%